Fatty acid analysis of Iranian junk food, dairy, and bakery products: Special attention to trans-fats - Nazari, Bahar (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Low attention to dairy product consumptions and high intake of junk foods and bakery products might be related to high prevalence of chronic diseases because of their fat content and fatty acid composition. OBJECTIVE: In this study we investigated the kind and amount of fatty acid content in Iranian junk foods, dairy, and bakery products MATERIALS AND METHODS: Some common brands of Iranian’s junk foods, dairy, and bakery products were chosen randomly from different supermarkets in Iran. The amount of 10 g sample was considered for fatty acid analysis by gas chromatography equipment with flam ionization detector. RESULTS: In this study stearic acid (C18:0) and palmitic (C16:0) acid have the highest amount among other saturated fatty acids in all groups. In junk foods and bakery products, the most common trans-fatty acid (TFA) is elaidic acid (C18:1 9t) with ranging from 2.4% to 18.5% and in dairy products vaccinic acid (C18:1 11t) has the high level of TFAs among others (2.1% to 11.5%). CONCLUSION: The amount of TFAs in Iranian junk foods and bakery products was in a high level.